Mother's emotions in the hospitalization of their newborns (Research, Society and Development, 2021)
Objective: To describe scientific productions that address the emotions and feelings of mothers during the hospitalization of newborns in Intensive Care Units. Methodology: integrative literature review, carried out with a time frame from 2016 to 2020. The abstracts of the articles were read and evaluated, and the productions that met the previously established search criteria were selected for the research. Results: Initially, sixteen articles were found, however, after applying the exclusion criteria, the final sample resulted in seven articles. Data analysis made it possible to classify publications into thematic categories: category A: Emotional confusion; category B: support network and category C: spirituality. Conclusion: It is concluded in this study that it is important to carry out works that aim to understand the feelings and experiences of people with family members in hospital, especially mothers and their newborns. Thus, in view of the emotions of this experience, create strategies in order to reduce situations that cause fear and anxiety.